The Role of AI in Ecohumanistic Education - Kovari , Attila; Andras , Istvan; Rajcsanyi-Molnar , Monika (Journal of Ecohumanism, 2024)
The paper discusses the potentials of ChatGPT and other AI technologies in diffusing ecohumanism in educational settings. Ecohumanism merges ecological and humanistic values to foster sustainable and ethical interactions between humans and the natural environment. Blended use of AI in education has the potential for paradigm changes in learning characteristics, personalizing experiences, and enhancing ecological literacy while bridging interdisciplinary collaboration. It illustrates, with the use of case studies from institutions like UC Berkeley, MIT, Stanford University, University of Edinburgh and University of Dunaujvaros, how AI tools may make learning environments engaging, effective, and ethically responsible. Some of the ethical and practical issues involved in the integration process are also spelled out along with AI, and it provides future research directions for maximizing the potential benefits that will result from the combination of AI with ecohumanistic education.